Prevalência e fatores de risco de asma e rinite em escolares de um município da mesorregião sudeste matogrossense - Nascimento, Alessandra Pinheiro Costa (2018)
Respiratory diseases such as asthma and allergic rhinitis are often associated and affect all ages, with greater magnitude in children and adolescents. Objective: To investigate the prevalence of asthma and rhinitis and the factors related to its development in schoolchildren living in the city of Primavera do Leste, Mato Grosso. Methods: The research was developed in two stages, one cross-sectional study (n = 3000) and another retrospective control case study (n = 1074). The assessment instruments were: the validated International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire to identify asthmatics in a sample of students from 19 public schools aged 6-7 and 13-14 years and structured questionnaire complementary to the investigation of associated socioenvironmental factors plus complementary questions that investigate socioeconomic data of the family, household characteristics and family exposure to pesticides. Results: 3,000 children were evaluated, the majority belonged to females (51.3%, n = 1540) and had a 13-14 age group (64.8%; n = 1945). In the 6-7 year age group, 101 (19.1%) asthmatic girls and 128 (24.2%) boys were found; for rhinitis 157 (29.7%) girls and 167 (31.6%) boys. In the 13-14 year age group, 168 (16.6%) asthmatic girls and 140 (15.0%) boys were found; for rhinitis 232 (22.9%) girls and 297 boys (31.8%). The diagnosis of active asthma was statistically higher in the 6-7 year age group among males than in 13-14 year olds. For rhinitis the prevalence found was higher in the girls, who stood out as being the most affected in both age groups. A positive association was observed between asthma in schoolchildren whose parents exercised household activity using a pesticide (male sex: p = 0.0003, χ 2 = 13.074, OR = 2.254, [CI 95% = (1.460-3.479) ], female: p = 0.0001, χ 2 = 14,824, OR = 2,441, [CI 95% = (1,556- 3,830)]). Schoolchildren whose parents worked in agriculture had a greater chance of developing asthma for both sexes, with greater significance in girls (p = 0.0013, χ 2 = 10,352, OR = 1837, [CI95% = (1.279-2.638) ], female: p = 0.0002, χ 2 = 13.955, OR = 2.029, [CI95% = (1.408-2.923)]). It was observed that 58.4% of the female students reported having had symptoms of rhinitis in the harvesting periods. Conclusions: The prevalence of asthma prevalence in the city of Primavera do Leste is high, but it does not differ substantially from the findings in Brazil and the State using the same instrument. Residing at the urban-rural border close to agriculture and pesticide management seems to pose a risk to schoolchildren. Of course, the conclusions of this work, far from being definitive, should serve to promote the widest debate possible on the subject.